Harmônicos na flauta transversal: uso didático e em performance - Alef Caetano Silva (2020)
This dissertation approaches several didactic, interpretative and performing uses that the harmonic emission technique has on the flute, and brings a brief account of Professor Ary Ferreira’s professional and personal lives, who was the first Brazilian to publish a thesis exclusively approaching harmonics in the transverse flute. In this research I will continue the study of the harmonics previously developed by FERREIRA (1944), with the aim of bringing didactic features to the approach of harmonics in the flute, as well as contributing to the dissemination and creation of didactic materials that have as a primary source the research of this great Brazilian flutist. This research is divided into four chapters. The first chapter clarifies the concept of the flute being an instrument of harmonic series, and elucidates the vibration modes in the strings and cylindrical tubes in a didactic way. The second chapter approaches the harmonics as a didactic and sound enhancement tool for the flutist, proposing a suggestion of classifying the exercises regarding the complexity of their execution. The third chapter explores the use of harmonics as timbre nuance by the composers and by the flutist as an interpreter and performer. Lastly, the fourth chapter approaches the use of harmonics as a difficult passage enabler during the performing and interpretative practice. The viability of this research occurred through bibliographical review regarding methods that approach harmonics as a performing and didactic tool, as well as bibliographical review of articles focused on flute performance pedagogy, and the accomplishment of interviews with flutist teachers of great relevance in the national scenario.